Pietism and community in Europe and North America : 1650-1850 - Strom, Jonathan (Brill's series in church history ;, 2010)
Pietist movements challenged traditional forms of religious community, group formation, and ecclesiology. Where many older accounts have emphasized the individual and subjective nature of Pietists to the exclusion of community, one of the hallmarks of Pietism has been the creation of groups and experimentation with new forms of religious association and sociality. The essays presented here reflect the diverse ways in which Pietists struggled with the tension between the separation from the "world" and the formation of new communities from the seventeenth to the nineteenth century in Europe and.